New Problems - New Solutions: A Never Ending Story - Hackl, W.O.; Ganslandt, T.; Section Editors for the IMIA Yearbook Section on Clinical Information Systems (Yearbook of Medical Informatics, 2016)
Objective: To summarize recent research and to propose a selection of best papers published in 2015 in the field of Clinical Information Systems (CIS).Method: The query which had been used last year to retrieve articles for the CIS section of the IMIA Yearbook of Medical Informatics 2015 was refined. It again aimed at identifying relevant publications in the field of CIS and comprised search terms from the Medical Subject Headings (MeSH) catalog as well as additional free text search terms from PubMed and Web of Science. The retrieved articles were categorized in a multi-pass review carried out separately by the two section editors. The final selection of 15 candidate papers was then peer-reviewed by Yearbook editors and external reviewers. Based on the review results the four best papers were then selected at the best papers selection meeting with the IMIA Yearbook editorial board. To get an overview on the content of the retrieved articles we applied text mining and term co-occurrence mapping techniques.Results: The query was carried out in mid-January 2016, yielding a combined result set of 1851 articles which were published in 790 different journals. The most relevant terms from abstracts and titles of these articles were assigned to six different clusters. A majority of articles dealt with two thematic blocks, problems and solutions in the CIS field. The majority of the 2016 CIS candidate papers and all four best papers could be assigned to these two thematic blocks.Conclusions: We identified two main tracks among the CIS candidate and best papers as well as in CIS research activities in general: problems and solutions. A never ending cycle of continuous improvement.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; clinical information systems